ANALISIS MULTIRESOLUSI WAVELET DENGAN TRANSFORMASI WAVELET DISKRIT BERBASIS GUI R (STUDI KASUS: INFLASI DI INDONESIA PADA PERIODE OKTOBER 2007-MEI 2018) - Sania Anisa Farah; Suparti Suparti; Dwi Ispriyanti (Jurnal Gaussian, 2020)
Lately, the wavelet applications are widely used in statistics, one of them is discrete wavelet transform (DWT) which is a non-parametric method for signal analysis, data compression, and time series analysis. As technology becomes more advanced, a software is necessary to support the statistical analysis by such method, one of them being the open source based R. It is often used in statistical computing with command line interface (CLI) which requires the R user to remember the names of syntaxes and functions. It becomes less effective when there are many related statistical analysis involved, so graphical user interface (GUI) is needed to access all of them easily. The testing of multiresolution analysis by DWT for Haar, Daublets, and Coiflets filters with levels 1-6 had been performed by using the inflation data in Indonesia during October 2007-May 2018 taken from Bank Indonesia website. The result shows that the sixth level of DWT gives the best estimation for each filters, and Daublets 20 is the best filter for overall estimation with MSE, MAPE, and MASE values are 0.05755, 3.40678, and 0.35343 respectively. The packages for GUI construction in R are wavelets and shiny. Based on its usage, the GUI is capable of processing the chosen analysis and showing the valid output.